INOVASI SAKPOLE (SISTEM ADMINISTRASI KENDARAAN PAJAK ONLINE) PADA PEMBAYARAN PAJAK KENDARAAN BERMOTOR DI SAMSAT SEMARANG II - Muhammad Iqbaal Maulana; Maesaroh Maesaroh; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
This study aims to determine and analyze the success of the Online Tax Vehicle Administration System (SAKPOLE) innovation in the payment of motor vehicle taxes at Samsat Semarang II, and the inhibiting factors for the Online Tax Vehicle Administration System (SAKPOLE) innovation. The method used in this research is descriptive qualitative method by conducting interviews and documentation. The data needed in this study are answers from informants related to innovation indicators on SAKPOLE innovation in motor vehicle tax payments. The results of the analysis and discussion in this study indicate that the implementation of SAKPOLE's innovation in motor vehicle tax payments has not been successful. This is because there are still several problems in each of the innovation indicators, including: the unavailability of an independent printing press at the Samsat Office, the SAKPOLE application can only be used on Android-based smartphones, people still have to come to the Samsat office to print STNK and stamp legalization , the public cannot upload files in the form of photos from the gallery, the verification process is quite long in the SAKPOLE application, network problems in remote areas, and the community is not thorough in understanding the SAKPOLE mechanism. Then for the inhibiting factor in SAKPOLE's own innovation, namely people who want to print SKPP but do not have a document in the form of an ID card in accordance with the STNK and there are no awards or incentives for employees.